In situ reversible underwater superwetting transition by electrochemical atomic alternation - Qianbin Wang (Nature Portfolio, 2019)
Materials with in situ reversible wettability have attractive properties for switching applications, but are a challenge to use especially for the inverse process of liquid spreading. Here, the authors propose an electrochemical strategy enabling in situ reversible superwetting conversion between underwater superoleophilicity and superoleophobicity by constructing a binary textured surface.